2017
DOI: 10.1142/s021881041750040x
|View full text |Cite
|
Sign up to set email alerts
|

Iatrogenic Injuries of the Palmar Branch of the Median Nerve Following Volar Plate Fixation of the Distal Radius

Abstract: Background: Our aims were to identify iatrogenous injuries to the palmar branch of the median nerve sustained during volar plate fixation of the distal radius, make the clinician aware of this relatively uncommon complication of distal radius fixation, to emphasise common threads in symptomatology and to propose an algorithm for evaluation and management. Methods: Retrospectively interrogating our database over a 5 year period, the case records, neurophysiology records, operative records, therapy records were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 37 publications
0
8
0
1
Order By: Relevance
“…Por otra parte, complicaciones graves como el síndrome de dolor regional complejo, el dolor de pilares, la cicatrización y la fibrosis se han relacionado con la lesión de RCP durante los abordajes de radio distal volar. Samson et al (2017) 21 identificaron siete pacientes con lesión iatrogénica de RCP durante la osteosíntesis de FRD volar a partir de una revisión retrospectiva de la base de datos de 5 años, dos de los cuales presentaban síntomas de SDRC. La RCP está ubicada en el lado radial del nervio mediano, cerca del tendón FCR a este nivel (►Figure 1).…”
Section: Discussionunclassified
See 1 more Smart Citation
“…Por otra parte, complicaciones graves como el síndrome de dolor regional complejo, el dolor de pilares, la cicatrización y la fibrosis se han relacionado con la lesión de RCP durante los abordajes de radio distal volar. Samson et al (2017) 21 identificaron siete pacientes con lesión iatrogénica de RCP durante la osteosíntesis de FRD volar a partir de una revisión retrospectiva de la base de datos de 5 años, dos de los cuales presentaban síntomas de SDRC. La RCP está ubicada en el lado radial del nervio mediano, cerca del tendón FCR a este nivel (►Figure 1).…”
Section: Discussionunclassified
“…On the other hand, serious complications such as complex regional pain syndrome, pillar pain, scarring, and fibrosis have been related to PCB injury during volar distal radius approaches. Samson et al (2017) 21 identified seven patients with iatrogenic PCB injury during volar DRF osteosynthesis from a retrospective 5-year database revision, two of them presenting CRPS symptoms. The PCB is located on the radial side of the median nerve, close to the FCR tendon at this level ( Figure 1 ).…”
Section: Discussionmentioning
confidence: 99%
“…[69][70][71] The PCB of the MN can be injured from iatrogenic causes or external trauma. 72,73 Patients with an injury to the PCB of the MN present with anterior wrist pain associated with paresthesias in the palm of the hand, which can mimic symptoms of CTS. Ultrasound can fully image the course of the PCB, which appears as a single hypoechoic fascicle.…”
Section: Posttraumatic Transection Of the Mnmentioning
confidence: 99%
“…Once in the subcutaneous tissue, the nerve continues distally superficial to the transverse carpal ligament to innervate the skin of the thenar eminence 69‐71 . The PCB of the MN can be injured from iatrogenic causes or external trauma 72,73 . Patients with an injury to the PCB of the MN present with anterior wrist pain associated with paresthesias in the palm of the hand, which can mimic symptoms of CTS.…”
Section: Lookalike Conditionsmentioning
confidence: 99%
“…(38,48,51,74,94,99,102,103) One large multi-institutional retrospective study by Satake et al identified 694 patients treated by volar locking plate, of which only 4 cases of tendon rupture (0.6%) were reported, while 18 cases of CTS (2.6%) and 3 cases of CRPS (0.4%) were reported, indicating a greater incidence of nerve complications than tendon complications. (93) Reported rates of hardware-related complications range from 0-7%, with malunion being the most frequent. (38,48,51,74,94,99,102,103) Some studies have also directly compared the outcomes of volar non-locking and volar locking plates.…”
Section: Volar Plate Specific Complicationsmentioning
confidence: 99%